Authoritarian Mothering Experiences of Top-Performing Senior High School Students in the Philippines: Impact on Psychological, Emotional, and Social Health - Arenas, Samantha Ashley C.; Carlos, Meya Pauline A.; Chua, Ryanne Pauline S.; Maceda, Danela Kayla T.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2022)
Parental influence is critical in shaping a child's growth and development. This phenomenological study examines the authoritarian mothering experiences of 15 top-performing Senior High School students in the Philippines and their psychosocial and emotional well-being. The data were analyzed thematically following the in-depth interviews. The findings indicate that the majority of informants were dissatisfied with the effectiveness of authoritarian parenting. This is because authoritarian mothering is detrimental to their health. The informants were experiencing psycho-emotional distress due to their exhaustion from their authoritarian mothers' constant pressure and rigid attitude. When it came to social relationships, authoritarian mothers lacked involvement in their children's psycho-emotional lives. The findings of this study could be used to develop effective mothering practices that balance academic success and the health of top-performing students.